Individualization of hypertension treatment: an expert review - Garg, Rajeev (International Journal of Advances in Medicine, 2023)
Management of hypertension is complex in patients with comorbid conditions and in those who are at high cardiovascular risk. Multiple guidelines recommend different treatment goals and therapeutic approaches for hypertension. In this review, we take an individualized management approach for hypertension with comorbidities mainly diabetes and chronic kidney disease (CKD), coronary artery disease, and for young patients and the elderly. Current evidence indicates a blood pressure goal of <130/80 mmHg for most patients with comorbidities except for the elderly aged >75 years in whom systolic pressure of 130-139 mmHg and diastolic pressure of 70-80 mmHg may be considered. For patients with diabetes and CKD, renin angiotensin aldosterone system (RAAS) inhibitors remain the initial choice of agents whereas in the young or elderly, any class including RAAS inhibitors, calcium channel blockers, and thiazide diuretics may be preferred. Special consideration is necessary for the elderly concerning the possible side effects of each drug class. In the presence of additional risk factors, an individualized approach is necessary to tailor the most effective therapy as per patient needs. Thus, in treating hypertension, a multipronged but individualized approach is necessary to optimize blood pressure control and clinical outcomes in the real-world setting.